Results of a hybrid cardiovascular rehabilitation program (in-hospital plus home) in patients with low income. (14th October 2021) - Garcia Saldivia, M; Ilarraza Lomeli, H; Rojano Castillo, J; Rius Suarez, M; Franco, M; Villegas, D; Negrete, D; Guerrero, T; Sandoval, C; Sanchez Cornejo, A; Ruan, J
Abstract: Background: One of the main problems facing cardiovascular rehabilitation (CR) is patient care and adherence. However, due to the low level of economic income of the patients who are cared for in our center, the possibility of going to CR in a conventional way is very difficult since they do not have the necessary resources to cover transportation, cost of the sessions, among others. It has been shown that the greater the number of sessions attended by the patient, the greater the reduction in cardiovascular risk, however the role of a hybrid program with a decreased number of face-to-face sessions has not been established. Purpose: Present the results of a hybrid training program (in-hospital plus home) in a low-income population. Education through supervised sessions plus home physical training in a patient with bases for exercise can improve their adherence with better results. Methods: A cohort of patients with heart disease who were referred to the Cardiovascular Rehabilitation program between May 2017 and February 2019 was included. The socioeconomic level was classified into 6 strata according to occupation, income, housing, economic dependents, place of origin and family health status. After risk stratification, the patients participated in a hybrid program that consisted of 6 in-hospital sessions, once a week, in which the training to be carried out at home was prescribed by means of a triptych. An exercise test was performed before and after completing the program, as well as psychological and nutritional intervention. Statistical analysis was performed using SPSS 21.0 software. All p values less than 0.05 were considered significant. Results: In the study period, of the total number of patients discharged for heart disease from the hospital, 61% were referred to cardiovascular rehabilitation, of which only 45% (n=39) completed the program, the reasons for dropping out were multiple and the lowest socioeconomic level (1) was the most frequent (figure 1). The main referral diagnosis was ischemic heart disease in 82%. The majority of patients were men, 95%. A significant improvement was observed in load METs, maximum heart rate, heart rate recovery (figure 2). Conclusion: The implementation of a hybrid cardiovascular rehabilitation program (in-hospital + home) was associated with an improvement in the exercise test parameters of patients who successfully completed the program. FUNDunding Acknowledgement: Type of funding sources: None.